The contrasting fortunes of pro-sovereignty currents in Basque and Catalan nationalist parties: PNV and CDC compared. Issue 4 (2nd October 2017) - Gillespie, Richard
ABSTRACT: The contrasting fortunes of pro-sovereignty currents in Basque and Catalan nationalist parties: PNV and CDC compared. Territory, Politics, Governance . Nationalist parties based on regions within European states have seen cases of major shifts from accommodation to sovereignty-based assertiveness in their positioning vis-à-vis central government. While these have been interpreted elsewhere mainly in terms of changes in contextual influences, the activity of groups within parties aiming to redefine territorial strategies has received much less attention, not least in the case of Spain. This comparison of factional politics within Basque and Catalan nationalist parties since the 1990s highlights the significant influence of party-level factors in affecting the prospects of a decisive strategic shift. Factors such as the loss of political power by a party, competition during processes of leadership succession, generational renewal and distinctive party cultures help explain why the outcomes of such efforts differ. Transformation has proved more difficult to achieve in the context of complex decentralized governance structures at regional level, as in the Basque Country. There, the existence of varying identity configurations, reflected in different political balances at the sub-regional level, provided an impediment to a thorough radicalization of the Basque Nationalist Party, whereas in Catalonia more centralized political arrangements facilitated the transformation of Democratic Convergence of Catalonia and its eventual commitment to independence.